GSTT1 and GSTM1 gene polymorphisims in sarcoidosis - Coskun, Funda; Karkucak, Mutlu; Yilmaz, Dilber; Yakut, Tahsin; Uzaslan, Esra (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Introduction: Sarcoidosis is a granulomatous disease of unknown cause, which affects all systems, especially the lungs and the lymphatic system. Genetic and environmental factors are held accountable for the etiology. Based on the general opinion, sarcoidosis develops after exposure to a specific environmental agent by genetically susceptible individuals.  The present study aimed to evaluate the disease susceptibility of the GSTT1 and GSTM1 gene polymorphisms in the patients with sarcoidosis. Method: The present study included 78 patients; 38 patients with histopathologically verified sarcoidosis and 40 control subjects. Multiplex PCR method was used to determine the GSTT1 and GSTM1 gene polymorphisms. The genotype was determined based on the bands formed in the agarose gel electrophoresis. The statistical analysis was done using the chi-square test. Results: The positive/negative genotype rates were 79%/21% and 53%/47%, respectively in the case group for the GSTT1 and GSTM1 gene polymorphisms, whereas the positive/negative genotype rates were 77%/23% and 55%/45% in the control group. There was no statistically significant difference in the positive and negative genotypes compared with the case group and the control group for the GSTT1 and GSTM1 gene polymorphisms (p > 0.05). Discussion: The results from the present study suggest that there is not any association with the control group for the disease susceptibility of the GSTT1 and GSTM1 gene polymorphisms in patients with sarcoidosis, and this result should be supported by large-scale studies because of the limited number of cases in the present study.